Graphene-based near-field optical microscopy: high-resolution imaging using reconfigurable gratings - Inampudi, Sandeep; Cheng, Jierong; Mosallaei, Hossein (Applied optics. Optical technology and biomedical optics, 2017)
High-resolution and fast-paced optical microscopy is a requirement for current trends in biotechnology and materials industry. The most reliable and adaptable technique so far to obtain higher resolution than conventional microscopy is near-field scanning optical microscopy (NSOM), which suffers from a slow-paced nature. Stemming from the principles of diffraction imaging, we present fast-paced graphene-based scanning-free wide-field optical microscopy that provides image resolution that competes with NSOM. Instead of spatial scanning of a sharp tip, we utilize the active reconfigurable nature of graphene's surface conductivity to vary the diffraction properties of a planar digitized atomically thin graphene sheet placed in the near field of an object. Scattered light through various realizations of gratings is collected at the far-field distance and postprocessed using a transmission function of surface gratings developed on the principles of rigorous coupled wave analysis. We demonstrate image resolutions of the order of λ /16 using computational measurements through binary graphene gratings and numerical postprocessing. We also present an optimization scheme based on the genetic algorithm to predesign the unit cell structure of the gratings to minimize the complexity of postprocessing methods. We present and compare the imaging performance and noise tolerance of both grating types. While the results presented in this article are at terahertz frequencies (λ =10  μm), where graphene is highly plasmonic, the proposed microscopy principle can be readily extended to any frequency regime subject to the availability of tunable materials.